2008
DOI: 10.1002/ijc.23468
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern and circulating levels of endostatin in patients with pancreas cancer

Abstract: Endostatin is a potent inhibitor of angiogenesis that is cleaved from the basement membrane protein type XVIII collagen. Expression of endostatin has recently been shown by Western blot analysis of tissue lysates in normal pancreas and pancreas cancer tissue. We show here that the expression pattern of type XVIII collagen/endostatin is shifted from a general basement membrane staining and is mainly located in the vasculature during tumor progression. This shift in type XVIII collagen/endostatin expression patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 35 publications
3
40
0
Order By: Relevance
“…We found that serum concentrations of VEGF, VEGF-D, VEGFR-2 and endostatin were significantly higher in patients with ductal adenocarcinoma than in healthy subjects, and these results are similar to those previously reported for VEGF (3) and endostatin alone (6). Furthermore, data on VEGF-D and VEGFR-2 have previously been reported only on pancreatic tissue and we now report these data for blood.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found that serum concentrations of VEGF, VEGF-D, VEGFR-2 and endostatin were significantly higher in patients with ductal adenocarcinoma than in healthy subjects, and these results are similar to those previously reported for VEGF (3) and endostatin alone (6). Furthermore, data on VEGF-D and VEGFR-2 have previously been reported only on pancreatic tissue and we now report these data for blood.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, vascular endothelial growth factor-D (VEGF-D) is one of the major factors associated with the growth of lymphatic endothelial cells (5). Finally, endostatin is a potent inhibitor of angiogenesis, and increased concentrations of this protein may be associated with cancer progression (6). Thus, several active and passive strategies appear to be adopted by tumor cells to determine the spread of the tumor from the primary site.…”
Section: Introductionmentioning
confidence: 99%
“…The altered expression pattern of type IV collagen observed in pancreas cancer tissue can therefore partly be due to disruption and reorganisation of pre-existing BMs in the tumour area by MMPs, but this would not wholly explain the expression pattern observed. The expression pattern of type XVIII collagen/endostatin, another component of the BM, is also altered in pancreas cancer (Ohlund et al, 2008). However, the expression pattern of type XVIII collagen does not resemble the expression pattern for type IV collagen in pancreas cancer.…”
Section: Discussionmentioning
confidence: 97%
“…In this process matrix metalloproteinases (MMPs) are involved in remodelling the basement membrane (Stallings-Mann and Radisky, 2007). We have previously shown an upregulated expression of MMP-3 and MMP-9 in pancreas cancer tissue (Ohlund et al, 2008), and interestingly both these proteases have type IV collagen as a substrate (Nyberg, 2005). The altered expression pattern of type IV collagen observed in pancreas cancer tissue can therefore partly be due to disruption and reorganisation of pre-existing BMs in the tumour area by MMPs, but this would not wholly explain the expression pattern observed.…”
Section: Discussionmentioning
confidence: 99%
“…Heparan sulfate proteoglycans (HSPGs), another mechanotransduction-associated surface protein, have been found to mediate progression of prostate cancer cells through modulation of production of ECMdegrading enzymes called matrix metalloproteinases (MMPs) [5]. Elevated MMP expression correlates to increased metastatic potential in numerous types of cancer; one hypothesis suggests that tumor cells adjust their MMP expression to increase the pore size of their ECM, allowing the cells to migrate easier and thereby facilitating tumor progression [6][7][8][9]. Pancreatic cancer cells (Panc-1) cultured on collagen hydrogels of increasing sti ness were shown to increase MMP activity [5].…”
Section: Microenvironmental Control Of Tumorigenesis: a Role For Matrmentioning
confidence: 99%